The diet of moreporks (Ninox novaeseelandiae) in relation to prey availability, and their roost site characteristics and breeding success on Ponui Island, Hauraki Gulf, New Zealand : a thesis presented in fulfilment of the requirements for the degree of Master of Science in Ecology at Massey University, Albany, New Zealand - Denny, Kirsty Marie (Massey University, 2009)
The ecological importance of introduced mammalian predators is well acknowledged in New Zealand, however, little research has focused on the ecology of native avian predators and their role in communities. This study investigated the ecology of moreporks (Ninox novaeseelandiae) on Ponui Island, Hauraki Gulf, New Zealand between August 2007 and April 2008. The primary aim was to investigate the functional response of moreporks to availability of their prey. The contents of regurgitated morepork pellets were compared with relative abundance of prey taxa (invertebrates, small birds and rodents) over the study period. The diet consisted primarily of a range of invertebrate prey, particularly weta (Anostostomatidae and Raphidophoridae) and beetles (Coleoptera). Small numbers of vertebrate prey were recorded including rodents and birds. A positive relationship between the percentage contribution to pellet samples of certain taxa and their relative availability was found, and there were peaks in the occurrence of seasonally abundant taxa including cicadas (Cicadidae), and huhu beetles (Prionoplus reticularis). The tendency of moreporks to prey on abundant taxa indicates that they are unlikely to depress prey populations to low levels, and may have some degree of stabilising influence. A significant increase in the rodent component of the diet in April indicated that the risk to moreporks of secondary poisoning during mammalian pest control operations may vary considerably with the time of year. The secondary aims were to collect data on roost site characteristics and breeding success. Moreporks roosted at a mean height of 4m, and foliar cover at the 4-6m height tier appeared to be the most important characteristic of roost sites when compared with control sites. These findings suggested that moreporks were selecting roost sites with high overhead cover. Possible reasons for this include predator avoidance, avoidance of mobbing passerines, and the microclimate provided. None of three established pairs and two other birds were observed to establish a nest or breed successfully. Additionally, only three juvenile moreporks were sighted or heard across the 90ha study area suggesting low breeding success in 2007-08. This may have been influenced by a range of factors including 1), predation by the high densities of ship rats on Ponui, or other predators 2), a lack of suitable nest sites such as tree hollows in some areas or 3), competition for invertebrate prey with high densities of ship rats and North Island brown kiwi (Apteryx mantelli).
Keywords: Predator-prey interactions; Avian predators; Fields of Research::270000 Biological Sciences::270700 Ecology and Evolution::270799 Ecology and evolution not elsewhere classified